Complete mitochondrial genome of the hybrid grouper Hyporthodus septemfasciatus (♀)×Epinephelus moara (♂) (Perciformes, Serranidae) and results of a phylogenetic analysis. Issue 3 (4th March 2021) - Kim, Yong Hwi; Park, Jong Yeon; Huynh, Duc Tam; Kim, Kang Rae; Bang, In-Chul
Abstract: The complete mitochondrial genome of the hybrid grouper Hyporthodus septemfasciatus (♀)× Epinephelus moara (♂) was obtained by next-generation sequencing. The mitochondrial genome was 16, 499 bp long, consisting of 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes, and a control region (D-loop). The overall base composition is 28.62% A, 28.27% C, 16.27% G, and 26.84% T with 55.46% A + T. In the maximum-likelihood (ML) phylogenetic analysis, the hybrid grouper belonged to the same clade as H . septemfasciatus (maternal inheritance).